Determinants of the impact of leadership styles on employees performance in Northern Region University, Malaysia - Lai, Mae Kwan (2024)
Many scholars have studied employee performance, but fewer studies have been conducted on higher education institutions, particularly in Malaysia's Northern Region. Determining the influence of leadership style on employee performance is the main goal of this study. Thus, this study aims to (i) to identify the relationship between autocratic leadership style and employee performance; (ii) to examine the relationship between democratic leadership style and employee performance; and (iii) determine the relationship between laissez-faire leadership style and employee performance. To examine the relationship between the variables, 346 surveys were distributed, and the responses were analysed using multiple regression, descriptive, and Pearson correlation techniques. The results of this study show that employees' performance is significantly impacted by the leadership styles of democratic and laissez-faire. Recommendations and implications for further research and practice were also discussed